Designing A Mobile Web-Based Culinary Tourism of Information System in Pringsewu District - Eka Ridhawati; Reni Astika; Yuri Fitrian (bit-Tech, 2023)
The rapid growth of information technology has significantly impacted various aspects of human life, offering immense importance and assistance in daily tasks. Information technology, with its swift and easy access to information, time and cost efficiency, and enhanced communication, has become an invaluable tool in numerous fields. In the culinary industry, leveraging information technology can elevate service quality, making operations more effective and efficient. This study focuses on the development of an information system for Nggruput Culinary Tourism in Pringsewu District. The research methodology adopufated for this project follows the waterfall model, ensuring a systematic and well-organized approach to the development of the Nggruput Culinary tourism information system. The implementation of this system is designed as a mobile web application, providing visitors with easy access to pertinent information about Nggruput Culinary Tourism. This mobile web-based approach aims to streamline marketing efforts for businesses and enhance public accessibility to comprehensive information about Nggruput Pringsewu Culinary. By employing a mobile web platform, the information system promises to offer a user-friendly interface for both businesses and the public, fostering efficient communication and interaction. The anticipated outcome is an improved marketing strategy for Nggruput Culinary Tourism, providing businesses with a competitive edge while ensuring that the public receives detailed and easily accessible information. This integration of information technology is poised to contribute positively to the advancement and effectiveness of Nggruput Culinary Tourism in Pringsewu District.